2022
DOI: 10.1080/21645515.2022.2140549
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of COVID-19 vaccine in lung cancer patients receiving anticancer treatment: A prospective multicenter cohort study

Abstract: This study assessed the immunogenicity and safety of the BNT162b2 mRNA vaccine in lung cancer patients receiving anticancer treatment. We enrolled lung cancer patients receiving anticancer treatment and non-cancer patients; all participants were fully vaccinated with the BNT162b2 vaccine. Blood samples were collected before the first and second vaccinations and 4 ± 1 weeks after the second vaccination. Anti-severe respiratory syndrome coronavirus-2 (SARS-CoV-2) spike protein S1 subunit receptor-binding domain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…Oncological patients suffered many consequences of the COVID-19 pandemic. In the initial phases of the pandemic, the accessibility to diagnostic and therapeutic pathways was impaired due to the conversion of several departments into COVID-19 units, causing disruptions to oncological screening, treatment, and surveillance [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Additionally, COVID-19 infection can cause serious complications in oncological patients undergoing chemotherapy or recovering from recent surgery [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oncological patients suffered many consequences of the COVID-19 pandemic. In the initial phases of the pandemic, the accessibility to diagnostic and therapeutic pathways was impaired due to the conversion of several departments into COVID-19 units, causing disruptions to oncological screening, treatment, and surveillance [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Additionally, COVID-19 infection can cause serious complications in oncological patients undergoing chemotherapy or recovering from recent surgery [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Articles that focused only on LC patients showed that COVID-19 mRNA and viral vectorbased vaccines can safely generate humoral immune responses in these patients, albeit at somewhat diminished levels compared to those in the general population. Out of the nine articles that specifically examine vaccine immunogenicity in LC patients, six demonstrate significant differences in median titers following the primary vaccination series when compared to HC data [29][30][31][33][34][35]. The variety of emerging and still-evolving Omicron variants of SARS-CoV-2, with the ability to overcome primary vaccination-induced immunity, present significant new threats to LC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that additional booster doses of the COVID-19 vaccination can improve on the inferior immunological effectiveness of the primary doses in patients with lung cancer. Five studies reported seroconversion rates (defined as the proportion of vaccine recipients whose blood titers for SARS-CoV-2 vaccine antibodies were higher than the test-specific lower limit cutoff value) of LC or thoracic cancer patients, at 93.7% [29], 95.2% [4,30], 98% [30], 99.1% [28], and 96.7% [31,32]. Mack et al [32] reported that LC patient Ab titers had a significantly reduced area under the curve per day compared to control antibody titers.…”
Section: Sars-cov-2 Vaccines Immunogenicity In Patients With Lc or Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies included healthy controls (HC) in the study cohorts, while two studies [ 4 , 28 ] did not employ controls. All studies accounted for the confounding factors of age, anticancer treatment, and steroid use, while most also included performance status and comorbidities [ 4 , 30 , 31 , 32 , 34 , 35 ]. Overall, after primary dose vaccination, patients with lung cancer showed lower seropositivity rates compared to healthy controls.…”
Section: Sars-cov-2 Vaccines Immunogenicity In Patients With Lc or Th...mentioning
confidence: 99%